A Little Trouble in the Yorkshire Dales B1 - MacAndrew,Richard; Nicholas Tims (United Kingdom Cambridge University Press, 2009)
This time Andy and Mary, are away with their father in the beautiful Yorkshire Dales in the UK. After discovering a locked door in a supposedly abandoned mine, Mary's curiosity is aroused. What is someone hiding in the mine? And who is the man watching them through the binoculars?
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents. with downloadable audio
Keywords: Language Learning; Fiction; Adventure; Lower-intermediate Level; Reading books